A fixation-click count signature as a visual monitoring enhancement feature for air traffic controllers - Wee, Hong Jie (2021)
This paper presents an approach to capture the deliberate perception and compre-hension behavior of Air Traffic Controllers (ATCOs) by utilizing their eyeball and hand movement. Hence, a new fixation-click count signature, involving ATCOs fixating on aircraft’s track or label, before performing respective commands within a specified operational duration, is derived. 88 one-hour real time simulations involving a remote eye tracker and scenarios mimicking actual air traffic were conducted for participants from three expertise levels. Results show that this signature is common amongst all participants for both incoming and outbound aircraft. Furthermore, addition visual attention span is required with increasing commands issued, as a higher fixation count is exhibited with more clicks performed for the one-hour duration. This signature could also be used to differentiate the expertise levels of ATCOs, as experts were found to exhibit the most fixation count across all click counts, followed by intermediates and novices.